Refuting the Narrative of Intolerance: A Historical and Empirical Analysis of Religious Harmony in Aceh - Khairil Fazal; Gina Widiya (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2026)
This study aims to refute the prevailing narrative of intolerance in Aceh by presenting a comprehensive historical and empirical analysis of religious harmony in the region. Aceh, widely known as the “Veranda of Mecca,” has often been portrayed in national and international discourse as an area with low levels of religious tolerance, particularly due to its implementation of Islamic law. However, this perception frequently overlooks the broader socio-historical and cultural context of Acehnese society. Using a qualitative descriptive-analytical approach that integrates historical, sociological, and literature-based methods, this research examines patterns of interreligious relations from the era of the Samudra Pasai Sultanate to contemporary Aceh. The findings reveal that values of tolerance, openness, and coexistence have long been embedded in Acehnese society, reflected in historical records of cross-cultural trade, the acceptance of foreign leaders, and the preservation of non-Muslim religious sites. Empirical evidence further demonstrates that interfaith harmony continues to be practiced in everyday life, supported by local wisdom such as peumulia jamee (honoring guests) and communal solidarity traditions. Case studies from various regions in Aceh, along with testimonies from community leaders and minority groups, indicate a high level of social cohesion and mutual respect among religious communities. This study argues that the narrative of intolerance in Aceh is largely shaped by external perspectives that tend to generalize isolated incidents without considering the region’s complex social realities. By integrating historical insights and contemporary empirical data, this research offers a more balanced understanding of Aceh as a society where Islamic values coexist with pluralism and universal human principles